Absolute eigenvalue diffusion tensor analysis for human brain maturation - Suzuki, Yuji; Matsuzawa, Hitoshi; Kwee, Ingrid L.; Nakada, Tsutomu (NMR in biomedicine, 2003)
The absolute eigenvalues of the diffusion tensor of white matter in sixteen normal subjects in two groups representing the early developmental stage (ages 1–10 years, n = 8) and young adult stage (ages 18–34 years, n = 8) were assessed using a high‐field (3.0 T) magnetic resonance (MR) system. All three eigenvalues, including the largest eigenvalue, decreased significantly with brain maturation. The rate of the decline in the two small eigenvalues was, however, much higher than that of the largest eigenvalue, resulting in an actual increase in fractional anisotropy, a commonly measured relative index. The data demonstrate that an increase in anisotropy associated with brain maturation represents a significant decline in the small eigenvalue components, rather than an increase in the largest eigenvalue. The observed pattern of eigenvalue changes is best explained by the simultaneous occurrence of two of several independent phenomena within the axonal microenvironment during the myelination process, namely, (1) decline in unrestricted water content in extra‐axonal space, and (2) increase in apparent diffusivity within the axon. Copyright © 2003 John Wiley & Sons, Ltd.